She writes in many-coloured headscarves! A conversation with Shelina Zahra Janmohamed. Issue 3 (2nd July 2016) - Girishkumar, Divya
Abstract: Shelina Janmohamed, the British Muslim writer and commentator, feels impatient with the stereotypic labels attributed by the West to Asian Muslim women. Through her memoir, Love in a Headscarf, she breaks out all the miserable images of what it is to be a British Asian Muslim woman, addressing issues that range from Asian marriages to Islamic terrorism and the question of the veil.